Study on the awareness and adoption of Shari‘ah governance framework 2010 by the Islamic financial institutions in Malaysia - Othman, Ahmad Azam; Hassan, Rusni; Omar, Muhammad Naim; Mohd Napiah, Mohammad Deen; Ariffin, Mahamad; Yusoff, Adnan (INSI Publications, 2012)
The Central Bank of Malaysia (hereinafter referred to as Central Bank) has introduced the guideline on Shari‘ah Governance Framework for Islamic Financial Institutions (hereinafter referred to as SGF 2010) in October 2010 to have proper Shari‘ah governance. The SGF 2010 has been circulated to all IFIs under the Central Bank jurisdictions to ensure the SGF 2010 is adopted accordingly. The effective date for adoption was on 1st January 2011, giving the IFIs six months to comply with. Within such period, the IFIs need to confirm that they have met all the requirements and are operating in accordance with it. Thus, this article investigates the awareness by the IFIs on the objectives of SGF 2010, perception on the applicability of SGF 2010 and level of adoption of SGF 2010 by the IFIs. This is done through the collection of data and information by distributing the questionnaire to the respondents who involved in IFIs’ industries such as the management of the IFIs, be it Islamic banks and Takaful institutions, Shari‘ah Committee and Shari‘ah Officers. Most of the data in this study were collected and analyzed using the Statistical Package for Social Sciences (SPSS) software version 16.0 and Microsoft Excel. Additional descriptive analysis is used to determine the number of frequencies and percentages. The findings and analysis show that the awareness amongst the respondents on the objectives of SGF 2010, their perception on the applicability of SGF 2010 and the level of adoption of SGF 2010 by the IFIs are very good and positive.